Legal Practice of Rural Revitalization in China - Zibi , Christophe Parfait (Khwopa Journal, 2025)
Rural revitalization is a national strategy of the Government of the People's Republic of China, the main aim of which is the overall development of rural areas. In concrete terms, the aim is to bring rural areas back to a level of sustained development, so that the population regains the desire and interest to return or remain there. This will inevitably involve agricultural development, industrial development, talent support, cultural prosperity, ecological protection, organizational construction, and integration between urban and rural areas. Of course, as with any public policy, this national strategy requires a legal framework. In this case, the Law on the Promotion of Rural Revitalization, which was promulgated by the Standing Committee of the National People's Congress and came into force on June 1st, 2021, embodies the Chinese government's vision in this area, in that it sets out the contours of the strategy, while providing a framework for it, via administrative and legal control.